The Ormoc Waterfront an integrated tourism and community center at Ormoc's gateway - Reyes, Karissa Ana Maria R. (College of Architecture, University of the Philippines Diliman, 2018)
The Ormoc Waterfront is a celebration and intersection of Ormocanon culture, community, heritage and the city's potential as the tourism gateway to Western Leyte. Based on a macro analysis of the city, the project's targeted agenda became centered on tourism, community engagement, and environmental quality. Derived from the three main agenda, the project's program consists of a port passenger terminal, visitor's center, museum, pasalubong center, community learning center, and public view decks facing vistas of the Ormoc bay. It aims to serve not only incoming tourists in the region, but also the local community. The site is located at the "gateway" of Ormoc city's main city center between the city's public market and the waterfront public park, currently separated by the Ormoc port. After a macro to micro analysis of the city and the chosen lot, the design problem that arose was: how to unite tourism and community at Ormoc's waterfront. The solution then became to both physically and programmatically connect these two. Physically, by means of ramps, bridges, and a large walkable roof that provide access and viewing decks for the public. Programmatically, by providing spaces that orient visitors, encourage interaction between the tourists and community, foster cultural appreciation and collective memory, offset built-up areas for public spaces, incorporate ormocanon elements in the design; ultimately spaces that give the Ormoc waterfront back to the people.